2017
DOI: 10.3847/1538-4357/835/1/39
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Study of the Build-Up of the Sun’s Polar Magnetic Field by Using a 3d Kinematic Dynamo Model

Abstract: We develop a three-dimensional kinematic self-sustaining model of the solar dynamo in which the poloidal field generation is from tilted bipolar sunspot pairs placed on the solar surface above regions of strong toroidal field by using the SpotMaker algorithm, and then the transport of this poloidal field to the tachocline is primarily caused by turbulent diffusion. We obtain a dipolar solution within a certain range of parameters. We use this model to study the build-up of the polar magnetic field and show tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 70 publications
3
49
0
1
Order By: Relevance
“…Tilts of these pairs are given by Joys law and no seed magnetic field is given in this simulation. (This study is very similar to the one presented in Section 4.2 of Hazra et al (2017).) Then we perform two more simulations.…”
Section: Sensitivity Of Solutions With Nonlinearitiesmentioning
confidence: 67%
See 2 more Smart Citations
“…Tilts of these pairs are given by Joys law and no seed magnetic field is given in this simulation. (This study is very similar to the one presented in Section 4.2 of Hazra et al (2017).) Then we perform two more simulations.…”
Section: Sensitivity Of Solutions With Nonlinearitiesmentioning
confidence: 67%
“…Because of this random component, the actual tilt angle in our model has a considerable variation. Since the poloidal field generated by the BL mechanism depends sensitively on the BMR tilt (Dasi-Espuig et al 2010;Jiang et al 2014;Hazra et al 2017), its random scatter gives rise to cycle variability. This greatly enhances the relatively modest cycle variability arising just from the random time delay (MT16).…”
Section: Results For Fixed Bmr Delay Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the SFT model, the only effect of meridional flow is the horizontal (poleward) transport of the surface magnetic field. However, some studies indicated the possible role of the vertical (radial) component of the meridional circulation for the evolution of the surface magnetic field (e.g., Dikpati & Choudhuri 1994;Hazra et al 2017). On the other hand, suggested that the effect of the vertical flow of the meridional circulation is suppressed when sufficiently strong downward magnetic pumping exists near the solar surface.…”
Section: Discussionmentioning
confidence: 99%
“…Разом з тим, в останні роки наступив ренесанс щодо ви-вчення поверхневого α-ефекту Бебкока-Лейтона. Виявилося, що механізм Бебкока-Лейтона заслуговує не меншої уваги [11][12][13][14][15][16][17], оскільки його властивості можна оцінити з статистичних властивостей спостережених сонячних плям на відміну від необхідності теоретичних розрахунків кінетичного параметру Паркера-Штеєнбека-Краузе.…”
unclassified